Synthesis and Spectral Characterization of 4-Hydroxy-3- Methoxybenzaldehyde Derivatives - Mohd Razip, Asaruddin; Sam, Ezekiel; Mohammad Farhan, Ariffeen; Md Abu, Affan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Vanillin plays an important role in flavouring and as aroma agent. Vanillin has been used as a chemical intermediate in pharmaceutical and chemical syntheses. Schiff base products have been proved to poses beneficial biological effect towards health. Fourteen vanillin derivatives were synthesized via Schiff base reaction using p-vanillin as the starting material reacted with 2-aminobenzenethiol, furan-2-carbohydrazide, 2- hydrazinylpyridine, 4-hydroxybenzohydrazide, acetohydrazide, benzohydrazide, (diphenylmethylidene) hydrazine, pyridine-4-carbohydrazide, benzene-1,2-diamine, phenylhydrazine, 2-hydroxybenzohydrazide, 1,3- benzothiazol-2-amine, 1-cyclohexylthiourea respectively. All of the compounds were characterized by elemental analysis, FTIR and 1H NMR.